Caracterização e controle biológico de Cercospora spp. em morangueiro (Fragaria X ananassa Duch.) - Krahn, Jaqueline Raquel Tomm (2023)
The strawberry (Fragaria X ananassa Duch.) is a species belonging to the group of small fruits and has great commercial importance, since its cultivation is predominant in family farming in different regions of the country, mainly in the states of Minas Gerais, Rio Grande do Sul, Paraná and Espírito Santo. Among the main diseases that affect the crop are leaf spots and currently, the control of these diseases is predominantly carried out by chemical fungicides. However, due to the fact that fruit consumption is mainly “in natura”, control alternatives involving clean technologies have been more used, and among them is biological control. Recently, the occurrence of a new foliar disease in strawberry plants was identified, with fungi of the genus Cercospora spp. Therefore, the general objective of this work was to characterize the pathosystem Cercospora spp. X strawberry and the action of different species of Trichoderma in controlling the disease. The specific objectives of the work were defined: a) to evaluate the pathogenicity, morphophysiologically and molecularly characterize the causal agent of Cercosporiosis in strawberry; b) to evaluate the “in vitro” and “in vivo” biocontrol of Cercospora spp. by the species T. harzianum and T. asperellum; c) Identify the compounds produced by the different species of Trichoderma; d) To identify the efficiency of using the antagonist, whether live organism or culture filtrates, under different forms of application in the control of Cercospora spp. For isolation of the pathogen, leaves with characteristic symptoms of Cercosporiose were collected in nine municipalities in Rio Grande do Sul and one in Santa Catarina. The isolates were evaluated morphophysiologically through mycelial growth, sporulation, conidia size and number of septa and then the data were submitted to the UPGMA grouping method (“Unweighted Pair Group Method with Arithmetic Mean”). Through the generated dendrogram, the isolates were grouped by the similarity between the means of the characters, from these, the molecular identification and the pathogenicity test of two isolates per group were performed. Molecular analysis indicated that Cercospora leaf spot on strawberry is caused by a complex of Cercospora spp. species, including C. kikuchii. The species of Trichoderma spp. were efficient in controlling the mycelial growth of Cercospora spp. both in culture pairing and by volatile and non-volatile metabolites. Isolates of Trichoderma spp. grown in liquid medium produced fatty acids and other organic compounds with fungicidal potential and activation of plant defense mechanisms. The application of Trichoderma spp., in the form of a live organism or filtered from culture, via leaves or in combination, was able to reduce the severity of Cercosporiosis, caused by Cercospora spp. in strawberry.